Importance of Incorporating Literature in the Language Classroom - Sharma, Lok Raj; Bhattarai, Rajendra; Humagain, Abhimanyu; Subedi, Shyam; Acharya, Hareram (Nepal Journal of Multidisciplinary Research, 2022)
Literature is a prolific expression of human feelings, emotions, thoughts, opinions, and so on. Language is a system of communication that consists of a set of sounds, words, and grammar rules that are used by a particular group of people. The relationship between language and literature is complex and multifaceted, with each influencing and enriching the other in a variety of ways. Literature can be an effective tool for improving language skills and deepening cultural understanding. The substantial objective of this article is to highlight the importance of incorporating literature in the language classroom. This article is based on the secondary qualitative data taken via books and journal articles regarding literature, language and the significance of literature for teaching language skills. Both teachers and students will be benefitted from this article as they will be encouraged and ignited to teach language in an innovative way through using literary texts. It will reflect how language by exploiting the authentic literary materials can be taught in real life situations.